Elevated Expression of miR-19b Enhances CD8+ T Cell Function by Targeting PTEN in HIV Infected Long Term Non-progressors With Sustained Viral Suppression - Yin, Lin-Bo; Song, Cheng-Bo; Zheng, Jie-Fu; Fu, Ya-Jing; Qian, Shi; Jiang, Yong-Jun; Xu, Jun-Jie; Ding, Hai-Bo; Shang, Hong; Zhang, Zi-Ning (Frontiers in Immunology, 2019)
Human immunodeficiency virus (HIV)-infected long-term non-progressors (LTNPs) are of particular importance because of their unique disease progression characteristics. Defined by the maintenance of normal CD4+T cells after more than 8 years of infection, these LTNPs are heterogeneous. Some LTNPs exhibit ongoing viral production, while others do not and are able to control viral production. The underlying basis for this heterogeneity has not been clearly elucidated. In this study, the miRNA expression profiles of LTNPs were assessed. The levels of microRNA-19b (miR-19b) were found to be significantly increased in peripheral blood mononuclear cells of LTNPs with lower rather than higher viral load. We made clear that miR-19b may regulate CD8+T cell functions in HIV infection, which has not been addressed before. Overexpression of miR-19b promoted CD8+T cell proliferation, as well as interferon-γ and granzyme B expression, while inhibiting CD8+T cells apoptosis induced by anti-CD3/CD28 stimulation. The target of miR-19b was found to be the “phosphatase and tensin homolog”, which regulates CD8+T cells function during HIV infections. Furthermore, we found that miR-19b can directly inhibit viral production in in-vitro HIV infected T cells. These results highlight the importance of miR-19b to control viral levels, which facilitate an understanding of human immunodeficiency virus pathogenesis and provide potential targets for improved immune intervention.